2007
DOI: 10.1007/s00406-007-0755-x
|View full text |Cite
|
Sign up to set email alerts
|

White matter hyperintensities and their associations with suicidality in patients with major affective disorders

Abstract: The increased prevalence of WMH in adults with major affective disorders and a history of suicide attempt, compared to similar patients without such a history, is consistent with previous findings in depressed children, youth and young adults. However, the association between WMH and suicidality holds true for both, depressed and bipolar patients. Our results suggest that WMH in patients with major affective disorders might be useful biological markers of suicidality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 36 publications
2
41
2
2
Order By: Relevance
“…79 As might be expected from the wide range of associated symptoms illustrated above, imaging studies have revealed very heterogeneous brain structural and functional changes related to suicide attempt; comprising the frontal, temporal, and the parietal cortices, and the subcortical structures. [36][37][38]80,81 Concordant with the suggestion that a broad array of mental impairments and neural abnormalities would be implicated in suicide, we observed that the occurrence of suicide in geriatric depression was associated with widespread, in contrast to circumscribed, reduction in GM and WM, when compared with patients with nonsuicidal depression. Significant decreases in the GM volume were seen in the frontal, medial frontal, parietal and temporal cortices, and the insula, midbrain, cerebellum, and lentiform nucleus of patients in the DS group.…”
Section: Suicidal Versus Nonsuicidal Geriatric Depressionsupporting
confidence: 84%
“…79 As might be expected from the wide range of associated symptoms illustrated above, imaging studies have revealed very heterogeneous brain structural and functional changes related to suicide attempt; comprising the frontal, temporal, and the parietal cortices, and the subcortical structures. [36][37][38]80,81 Concordant with the suggestion that a broad array of mental impairments and neural abnormalities would be implicated in suicide, we observed that the occurrence of suicide in geriatric depression was associated with widespread, in contrast to circumscribed, reduction in GM and WM, when compared with patients with nonsuicidal depression. Significant decreases in the GM volume were seen in the frontal, medial frontal, parietal and temporal cortices, and the insula, midbrain, cerebellum, and lentiform nucleus of patients in the DS group.…”
Section: Suicidal Versus Nonsuicidal Geriatric Depressionsupporting
confidence: 84%
“…Thirty-five of these studies evaluated the presence of hyperintensities in bipolar patients. Applying the five a priori criteria to these studies, eight studies were excluded: four (Breeze et al, 2003; Deicken et al, 1991; Hickie et al, 1995; Pompili et al, 2007) were excluded because the hyperintensity data reported was not differentiated by the specific psychiatric diagnosis; three (Botteron et al, 1992; Böhm et al, 2006; Zanetti et al, 2007) were individual case reports; and one (Kato et al, 2000) did not include a control group. Finally, of the 27 studies meeting criteria for meta-analysis, six of these were excluded (see Table II).…”
Section: Resultsmentioning
confidence: 99%
“…Dupont et al (1987, 1990) noted a trend toward increased depressive symptoms in subjects with greater hyperintensities, but Gulseren et al (2006) did not. Pompili et al (2007) reported that WMH were associated with history of suicide attempts.…”
Section: Discussion and Reviewmentioning
confidence: 99%
“…Although the pathogensis of these lesions is not completely understood, at least some are likely to reflect vascular ischaemia and are associated with cardiac risk factors and normal ageing (Breeze, Hesdorffer, Hong, Frazier, & Renshaw, 2003). They appear particularly significant in affective disorder, having being associated both with late-onset depressive illness (Sneed, Roose, & Sackeim, 2006) and high rates of suicidality (Pompili et al, 2007).…”
Section: White Mattermentioning
confidence: 99%